PULSATIONAL AND ORBITAL PERIODS OF SMALL-AMPLITUDE CEPHEID SU CAS - Usenko, I. A.; Klochkova, V. G.; Tavolzhanskaya, N. S. (Одеські астрономічні публікації, 2007)
New seven high-resolutional spectra of small-amplitude Cepheid SU Cas have been obtained to determine its atmosphere parameters (Teff=6384 K; log g=2.4; Vt=3.3 km s-1) and to measure its radial velocities. The last ones were added to the total list (360 values) and using the frequency analysis we can specify the pulsational and orbital periods of this Cepheid. With the well-known main pulsational period of 1.949329 days, classified as fundamental tone, we can detect the presence of two equidistant periods at a distance of ±0.003 c/d from it, and the secondary (possible first overtone) one of 2.040461 day. Their ratio P1/P0 = 0.96 supposed about an an existence of non-radial pulsations in the Cepheid’s atmosphere. Changes of the mean colour-index, effective temperature and γ-velocity confirmed the presence of one or more companions with possible periods of 463.7 - 483.8, 1738.8 and 7490.3 days.